2015
DOI: 10.1080/19491034.2015.1035844
|View full text |Cite
|
Sign up to set email alerts
|

ESCRTs breach the nuclear border

Abstract: T he endosomal sorting complexes required for transport (ESCRT) are best known for their role in sorting ubiquitylated membrane proteins into endosomes. The most ancient component of the ESCRT machinery is ESCRT-III, which is capable of oligomerizing into a helical filament that drives the invagination and scission of membranes aided by the AAA ATPase, Vps4, in several additional subcellular contexts. Our recent study broadens the work of ESCRT-III by identifying its role in a quality control pathway at the nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 58 publications
(66 reference statements)
0
11
0
Order By: Relevance
“…[26][27][28] The ESCRT machinery was originally described as a vacuole-sorting complex, 29 and subsequently recognized to mediate many additional cellular processes, such as plasma membrane repair, cytokinetic abscission, viral budding at the plasma membrane, endocytosis and secretion, and NPC insertion into the NE. [30][31][32] In all of these processes, the ESCRT machinery mediates the membrane remodeling by promoting membrane curvature and, in most cases, driving membrane scission. The ESCRT machinery consists of multiple subunits, ranging from ESCRT-0 to ESCRT-III.…”
Section: Escrt-iii Proteins Mediate Nuclear Membrane Repairmentioning
confidence: 99%
“…[26][27][28] The ESCRT machinery was originally described as a vacuole-sorting complex, 29 and subsequently recognized to mediate many additional cellular processes, such as plasma membrane repair, cytokinetic abscission, viral budding at the plasma membrane, endocytosis and secretion, and NPC insertion into the NE. [30][31][32] In all of these processes, the ESCRT machinery mediates the membrane remodeling by promoting membrane curvature and, in most cases, driving membrane scission. The ESCRT machinery consists of multiple subunits, ranging from ESCRT-0 to ESCRT-III.…”
Section: Escrt-iii Proteins Mediate Nuclear Membrane Repairmentioning
confidence: 99%
“…While no single dedicated membrane bending or fusion machinery has been identified that drives nuclear pore formation, an emerging theme is the cooperative action of nups containing amphipathic helices or reticulon domains capable of recognizing and/or generating membrane curvature (Marelli et al, 2001;Drin et al, 2007;Dawson et al, 2009;Chadrin et al, 2010;Doucet et al, 2010;Vollmer et al, 2012Vollmer et al, , 2015von Appen et al, 2015;Casey et al, 2015;Floch et al, 2015;Mészáros et al, 2015). Interestingly, budding yeast requires the membrane bending and scission endosomal sorting complexes required for transport (ESCRT)-III proteins to ensure formation of functional NPCs, raising the possibility that an established multifunctional membrane remodeler that acts during pore biogenesis may yet be identified (Webster et al, 2014;Webster & Lusk, 2015). Consistent with this idea, genetic ablation of ESCRT-III components and the AAA-ATPase Vps4 leads to the accumulation of defective NPCs in a compartment called the storage of improperly assembled NPCs compartment (SINC), which is subsequently retained in mother cells (Webster et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1B). Last, an exciting possibility would invoke a model in which ESCRTs clear misassembled nups through a vesicular intermediate within the NE lumen[62](Fig. 1B) in a mechanism analogous to herpesvirus nuclear egress[63].…”
Section: Maintaining the Ne Barrier With Escrtsmentioning
confidence: 99%